Reconstructing developmental lineages: a retrospective approach using somatic mutations and variant allele frequency - Sajjad, Mahnoor; Kwon, Seong Gyu (Frontiers in Genetics, 2026)
Somatic mutations accumulate during the first zygotic division and continue throughout an organism’s lifespan. The characteristics and frequency of these mutations are contingent on developmental timing and tissue type, giving rise to somatic mosaicism, defined as the presence of unique genomic alterations across different cells. They serve as endogenous cellular barcodes, enabling detailed reconstruction of cell lineages and clonal dynamics. Although lineage tracing techniques have advanced from early microscopic observation and dye staining to the introduction of artificial barcodes via gene editing, owing to ethical considerations, such genetic manipulations in human developmental research are unavailable. Therefore, spontaneously arising somatic mutations are the most suitable strategy for tracing human lineages. Current approaches can be broadly categorized into two strategies: (i) high-resolution methods, including single-cell clonal expansion or laser-capture microdissection, which construct precise phylogenetic trees based on shared mutation profiles; and (ii) bulk sequencing methods, which infer lineage proximity by comparing variant allele frequencies across samples. As more lineage-tracing studies are being conducted focusing on a wider variety of organs, the integration of such data will make it possible to discover the general principles governing human development. This review highlights how the concept of somatic mutations has been applied across diverse biological contexts and discusses the insights and common principles that can be drawn from these findings.